2022
DOI: 10.14710/jai.v0i0.47064
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jenis Kelamin, Usia, dan Data Antropometrik terhadap Landmark Blok Popliteal

Abstract: Latar belakang: Teknik blok popliteal menggunakan stimulator saraf masih menjadi pilihan di Indonesia. Keberhasilan blok meningkat jika pengetahuan dan pemahaman landmark anatomi baik. Landmark anatomi berupa jarak titik percabangan saraf skiatik terhadap lipatan fossa popliteal dan kedalaman titik tersebut dari kulit. Perbedaan landmark anatomi dapat terjadi karena perbedaan ukuran tulang panjang dan massa otot. Penelitian ini bertujuan mengetahui pengaruh jenis kelamin, usia, dan data antropometri terhadap l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…At the same time, other factors such as gender, age, and education do not show a strong and consistent influence. The results of these statistical tests are researched by Rizali et al (2017) in determining the amount of WTP for clean air found that the characteristics of respondents significantly influenced the amount of WTP, thus indicating a relationship that requires further exploration in the context of wetland agriculture (Anshari et al, 2023; Rizali et al, 2017) as well as Tantri et al (2022) in a study to investigate the influence of gender, age, and anthropometric data on popliteal block landmarks, presenting a research approach that considers various characteristics of respondents, which can be applied to study the determinants of WTP(Tantri et al, 2022). WTP calculation for agricultural wetland at Banjar Regency…”
mentioning
confidence: 99%
“…At the same time, other factors such as gender, age, and education do not show a strong and consistent influence. The results of these statistical tests are researched by Rizali et al (2017) in determining the amount of WTP for clean air found that the characteristics of respondents significantly influenced the amount of WTP, thus indicating a relationship that requires further exploration in the context of wetland agriculture (Anshari et al, 2023; Rizali et al, 2017) as well as Tantri et al (2022) in a study to investigate the influence of gender, age, and anthropometric data on popliteal block landmarks, presenting a research approach that considers various characteristics of respondents, which can be applied to study the determinants of WTP(Tantri et al, 2022). WTP calculation for agricultural wetland at Banjar Regency…”
mentioning
confidence: 99%
“…At the same time, other factors such as gender, age, and education do not show a strong and consistent influence. The results of these statistical tests are researched by Rizali et al (2017) in determining the amount of WTP for clean air found that the characteristics of respondents significantly influenced the amount of WTP, thus indicating a relationship that requires further exploration in the context of wetland agriculture (Anshari et al, 2023; Rizali et al, 2017) as well as Tantri et al (2022) in a study to investigate the influence of gender, age, and anthropometric data on popliteal block landmarks, presenting a research approach that considers various characteristics of respondents, which can be applied to study the determinants of WTP(Tantri et al, 2022). WTP calculation for agricultural wetland at Banjar Regency…”
mentioning
confidence: 99%